Mild anterior displacement of the anus as a cause of Constipation: introducing a new modality for diagnosis. - Javad Nasiri; Fariba Jahangiri; Seyed Mojtaba Moussavi-khoshdel (Pediatric Surgery Research Center of Shahid Beheshti University of Medical Sciences, 2018)
Introduction: Mild anterior displacement of the anus may be a cause of constipation. Routinely for detection of the anterior anus, the mean anal position index is used but in this study we introduce another modality for this purpose. Material and Methods: In this prospective study, patients with intractable constipation with onset bellow one year of age, normal rectal manometry, normal rectal biopsy and abnormal shape of anal verge, were include. The location of the anus was checked by muscle stimulator and according to the severity of the anteriority mini anorectoplasty or simpleY-V transposition of the anus was performed. Results: Ten patients were studied. All were female with a mean age of 7 months. In 2 cases anorectoplasty and in the others Y-V anoplasty was done. All patients ultimately were cured. Conclusion: Using muscle stimulator in external sphincter is reliable for detection of anterior displacement of the anus. Anorectoplasty or Y-V anoplasty for resolving constipation in these patients are effective.